An Application Of Statistical Quality Control On Process Improvement: Case Study In Stayrod Manufacturing - Norhidayah, Mohamed Hussin (2010)
This project was conducted at Jati Beringin Sdn. Bhd (SME Industry). This company is one of the steel industries in Malaysia. This study identified the problems that face regarding quality control in the production. The primary data include gathering data from the production department while the secondary data are archival collections such as information from journals, reference books, internet resources, and articles. Statistical process controls such as control chart and process capability were applied to analysis the data collected. From the analysis, it showed that the first three processes i.e. cutting. forging and deburring were in control. In terms of process capability. these processes were capable to produce as specification required. This specification is based on the customer requirements. However, for pressing and threading processes, there are probability 0.25 out of 5 which roughly 5% for pressing product rejected and 0.5 out of 5 which roughly 10% of the threading product are rejected. If the quality control is used properly by the company and used as a feedback, it may contribute to company competitive advantages. Besides that, the company also can achieve the customer expectations and satisfaction by providing products with minimal defect, and good service.